Physical and emotional health in the patients with diabetes mellitus - A. S. Soplevenko (Кубанский научный медицинский вестник, 2014)
Psycho-emotional state of 94 patients with diabetes mellitus in connection with clinical characteristics of the diabetes was investigated. The following factorial connections were established: 1) between age and health-feeling and mood; 2) between sex differences and health-feeling and activity; 3) between type of diabetes and health-feeling and mood; 4) between a hyperglycemia and activity; 5) between type of therapy (insulin therapy, sulfonylureas, therapy for complications) and health-feeling and mood.